Exploring educational experiences that correlate with self-directed learning in college students seeking to pursue science, technology, engineering, math, and medical (STEMM) fields - Kemp, Kyeorda L.; Davidson, Cameron J.; Hurse, Deidre N.; Naik, Akshata R. (Frontiers in Education, 2024)
Educational experiences available to high school students have the potential to provide learning opportunities within science, technology, engineering, mathematics, and medicine (STEMM) that lead to student success in college and beyond. Therefore, the goal of our research was to identify whether participation in STEMM-specific outreach and pathway programs (OPP), advanced placement/international baccalaureate (AP/IB), or dual enrollment correlate with self-directed learning (SDL) skills. Our population is composed of recent high school graduates matriculating into STEMM focused college programs. We collected responses from 339 students nationwide to assess their (1) experience with SDL, (2) the behavioral trait for SDL, and (3) the application of SDL in a newly developed situational judgment case. Our results demonstrate that those who have OPP experiences did not differ from their non-OPP counterparts regarding any aspect of SDL. However, dual enrollment significantly correlates with experience with components of SDL (r= 0.206, p<0.001). Interestingly, AP/IB significantly correlates with the SDL behavioral trait (r= 0.145, p<0.05) as well as the application of SDL skills (r= 0.202, p<0.001), but not SDL experiences. This work identifies opportunities for improving the development of SDL within external and internal educational experiences for students interested in pursuing a career in STEMM.